THE EFFECTIVENESS OF ENHAII TRAINEES’ ENGLISH COMMUNICATION TOWARDS THE CUSTOMERS’ UNDERSTANDING - Retno Budi Wahyuni; Naniek Kuswardhani (Universitas Negeri Padang, 2016)
The trainees’ English speaking skill ability at Enhaii hotel can not be separated from their knowledge of language functions in hotel service business. Enhaii Hotel is a training hotel for hospitality students of STP Bandung. It is identified that sometimes the trainees use inappropriateness of vocabularies and English terms. In other words, there is sometimes misunderstanding between the trainee and the guests. This research is aimed to describe the customers’ understanding level towards trainees’ technical terms and vocabularies chosen in a hotel business. Therefore, it is used as the basis of improving the trainees’ quality communication service at Enhaii Hotel Bandung. The writers use observation technic to identify the effectiveness and appropriateness of vocabularies and terms chosen in serving the hotel guests.